Agro-processed foods and beverages export market study UK, Netherlands, USA, Canada (CEDP St. Michael, BarbadosBB, 1992)
Contains profiles for 19 product sectors covering market opportunities for the four countries identified. Profiles focus on key market trends and the factors stimulating change and driving growwth; possible market niches amongst specific groups of consumers; key players and suppliers; and specific market requirements or barriers to market access.
DC